ASSOCIATION BETWEEN ECHINOID AND SEAGRASS COMMUNITY IN DERAWAN ISLAND WATERS - Roem, Muhamad; Setianingrum, Retno; Weliyadi, Encik (Journal of Aquatropica Asia, 2022)
Sea urchins a biota that is often associated with seagrasses were often found in seagrass beds. The objectives of this research were to discover the condition of sea urchins and seagrass, such as diversity, uniformity, dominance in sea urchins, density, and cover on seagrass, and related to variables in this research. This research was conducted on Derawan Island. The research method that was used is a 5m x 5m (sea urchin) quadrate and 0.5m x 0.5m (seagrass) placed intentionally on 2 stations with a total of 30 quadrats. The results found 3 species of sea urchins and 4 species of seagrass. At station 1 abundance of sea urchins is 2.94 individual/m2 whereas at station 2 is 0,28 individual/m2. At station 1 seagrass density 117,33 shoot/m2 whereas station 2 is 120,13 shoot/m2. Seagrass cover at station 1 is 58,75% and at station 2 is 60,28%. The dominant sea urchin species is Diadema setosum with the following diversity values H'=0,36, E=0,3, and C=0.81. There was no significant difference between variables at each station except temperature (0.020<0.05) and DO (0.027<0.05). Variables that were correlated with sea urchins in the seagrass ecosystem are nitrate, salinity, phosphate, temperature, and pH. The association with seagrasses in Derawan Island is positive.